Why branded hotels can outperform non-branded competitors - Milburn, Robert (Henry Stewart Talks, 2009)
What is a brand?, Intangible value of brands, It is all about market share, Price, Brands can generate higher performance, Branded versus non-branded hotels, What is a brand worth?, Willingness to pay for brand, Brand owners spend more on advertising and PR, Branded hotel performance versus unbranded, Brands can deliver value, Does new technology advantage brands?
Archived at 2025/05/28